Eupatolide Inhibits PDGF‐induced Proliferation and Migration of Aortic Smooth Muscle Cells Through ROS‐dependent Heme Oxygenase‐1 Induction. (8th January 2013) - Kim, Namho; Hwangbo, Cheol; Lee, Suhyun; Lee, Jeong‐Hyung
<x xml:space="preserve">Abstract</x> The abnormal proliferation and migration of vascular smooth muscle cell (VSMC) contributes importantly to the pathogenesis of atherosclerosis and restenosis. Here, we investigated the effects of eupatolide (EuTL), a sesquiterpene lactone isolated from the medicinal plant Inula britannica, on platelet‐derived growth factor (PDGF)‐induced proliferation and migration of primary rat aortic smooth muscle cells (RASMCs), as well as its underlying mechanisms. EuTL remarkably inhibited PDGF‐induced proliferation and migration of RASMCs. Treatment of RASMCs with EuTL induced both protein and mRNA expression of heme oxygenase‐1 (HO‐1). SB203580 (a p38 inhibitor), SP600125 (a JNK inhibitor), U0126 (a MEK inhibitor) and LY294002 (a PI3K inhibitor) did not suppress EuTL‐induced HO‐1 expression; however, N‐acetylcysteine (NAC, an antioxidant) blocked EuTL‐induced HO‐1 expression. Moreover, treatment of RASMCs with EuTL increased reactive oxygen species (ROS) accumulation and nuclear translocation of nuclear factor‐E2‐related factor 2 (Nrf2); however, this translocation was also inhibited by NAC. NAC or inhibition of HO‐1 significantly attenuated the inhibitory effects of EuTL on PDGF‐induced proliferation and migration of RASMCs. Taken together, these findings suggest that EuTL could suppress PDGF‐induced proliferation and migration of VSMCs through HO‐1 induction via ROS‐Nrf2 pathway and may be a potential HO‐1 inducer for preventing or treating vascular diseases. Copyright © 2013 John Wiley & Sons, Ltd.